Problematika Hukum Akibat Perkawinan Campuran Terhadap Status dan Hak asuh Anak Dibawah Umur - Ajeng Sholikhawati; Echa Nursyah Dani Sumadi; Ilham Firmansyah; Nugroho Dwi Saputro (LPPM Universitas Sains dan Teknologi Komputer, 2024)
This journal discusses the problematic status and custody rights of children with the protection of child welfare after the divorce of different nationalities. The research method we used is Normative Juridical research with an approach based on understanding theories, concepts, legal principles, and regulations related to the research conducted. According to our research results, the problem in mixed marriages involves disputes related to child custody and their nationality status. Although there are regulations that stipulate children's rights, after a divorce, children's rights are not sufficiently guaranteed legally. Therefore, special regulations are needed as a guarantee and supervision so that children's rights can be protected and fulfilled after a divorce.